Active Learning on Teaching Arabic for Special Purpose in Indonesian Pesantren. (2nd June 2015) - Yusuf, Muhammad; Wekke, Ismail Suardi
Abstract: Indonesian society gains support from private institution in participating to teaching and learning process as national education system. It tried to implement many approach in conducting process of learning. Furthermore, this research would explore how pesantren in performing active learning during teaching foreign language such Arabic for special purpose. Qualitative approach was employed in conducting research. In-depth interview and participant observation were applied to collect data. One of the options to maintain the educational activities is active learning during language enhancement. Kiyai (teacher) and santri (student) decided to start active learning as the approach. They construct programs and activities in enhancing students' language skill. Furthermore, teacher, instructor and peer-trainer explore opportunities for every individual to have a sufficient training during language week. It shows that there is no program that suits for everyone. Therefore, teacher boards create many programs in pursuing learning outcomes. Furthermore, they observe learning achievement morning to evening, during pray time. The programs were not only realized in the classroom but also in the kitchen, dormitory and other functional room. Finally, this model in religious institutions is a model on creating educational environment as a medium of interaction to accelerate process of learning.